2021
DOI: 10.1038/s41597-021-01085-5
|View full text |Cite
|
Sign up to set email alerts
|

A dataset of dual calcium and voltage optical mapping in healthy and hypertrophied murine hearts

Abstract: Pathological hypertrophy underlies sudden cardiac death due to its high incidence of occurrence of ventricular arrhythmias. The alteration of transmural electrophysiological properties in hypertrophic cardiac murine tissue has never been explored previously. In this dataset, we have for the first time conducted high-throughput simultaneous optical imaging of transmembrane potential and calcium transients (CaT) throughout the entire hypertrophic murine hearts at high temporal and spatial resolution. Using Elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In vitro experimental models of cardiomyocyte and non-myocyte stretch resulted in cell hypertrophy and hyperplasia, induction of protein synthesis and increased expression of prohypertrophic proto-oncogenes such as fos, jun, myc, Ha-ras, and genes encoding atrial natriuretic factor and β-myosin heavy chain [ 116 118 ]. This was recapitulated in murine and porcine studies of hypertension and volume overload where transcription of prohypertrophic genes, and development of LVH were observed [ 119 123 ].…”
Section: Pathogenesis Of Ckd-associated Cardiomyopathymentioning
confidence: 94%
“…In vitro experimental models of cardiomyocyte and non-myocyte stretch resulted in cell hypertrophy and hyperplasia, induction of protein synthesis and increased expression of prohypertrophic proto-oncogenes such as fos, jun, myc, Ha-ras, and genes encoding atrial natriuretic factor and β-myosin heavy chain [ 116 118 ]. This was recapitulated in murine and porcine studies of hypertension and volume overload where transcription of prohypertrophic genes, and development of LVH were observed [ 119 123 ].…”
Section: Pathogenesis Of Ckd-associated Cardiomyopathymentioning
confidence: 94%
“… 56 Dual mapping enables voltage–Ca 2+ coupling analysis, including voltage–Ca 2+ latency, important for elucidating arrhythmic risk. 57 …”
Section: Principles Of Optical Mappingmentioning
confidence: 99%
“…fluoVolt) has increased single wavelength penetration depths from 0.5–1 mm using standard (green–red) dye to ∼1–4 mm in cardiac tissue using ‘near-infrared optical mapping’. 29 , 77 Previously, studies used cardiac wedge preparations or myocardial slices to provide a 2D transmural surface 10 , 57 or two CCD cameras on either side of the myocardium in ventricular wall preparations. 78 Mitrea et al 79 applied near-infrared di-4-ANBDQBS for improved transillumination to record signals from four different layers of the myocardial wall.…”
Section: State-of-the-art Applications Of Optical Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies report AP-CaT activation delay or repolarization latency (often reported as a phase plot, AP-CaT delay trace) to provide information on excitation-contraction coupling 5,50,51 . KairoSight-3.0 allows for robust AP-CaT coupling mapping across the surface of the cardiac preparationduring both activation and repolarization.…”
Section: Ap-cat Couplingmentioning
confidence: 99%